Estudo da toxicidade e da atividade anti-inflamatória do chá e dos polissacarídeos obtidos das cascas de Ximenia americana L. em modelos de inflamação aguda e artrite induzidos por zimosan em roedores - Marques, Gabriela Fernandes Oliveira (2020)
Rheumatoid arthritis (RA) is a severe arthropathy that affects 0.5-1% of world population, characterized by peripheral joints impairement, persistent synovitis and pain. The therapeutical approach of this pathology includes anti-inflammatory/analgesic drugs and implies high costs, and involving serious side effects. The use of medicinal plants has been a universal popular practice, which enables them as tools of ethnopharmacological studies. Ximenia americana (Olacaceae family) or “ameixa-do-sertão” is used popularly in Northeast Brazil, contains a diversity of bioactive compounds, including polysaccharides. Several parts of the plant are used in folk medicine to treat inflammatory and/or painful disorders. Studies involving experimental models of acute and chronic inflammation in rodents, have demonstrated anti-inflammatory action of its aqueous and hydroethanolic extracts. Additionally, the aqueous extract and the polysaccharide fractions showed antinociceptive action in a model of pancreatitis in mice. In addition, tea of the barks inhibits inflammatory parameters in an experimental gastritis model. Thus, this study focuses on investigating the effect and mechanisms involved in the anti-inflammatory action of tea and polysaccharides from the barks of Ximenia americana in models of acute inflammation and arthritis induced by zimosan, as well as the toxicity resulting from its treatment. Tea (50, 100, 150 mg/kg; v.o.), containing carbohydrates (44.8%) and polyphenols (28.3%); and polysaccharide fractions (FI, FII: 1 mg/kg; e.v.) were administered to Swiss Mice before (induction of edema or peritonitis) or to Wistar Rats after (arthritis induction) stimulation with zimosan. Then, the evaluations of the inflammatory parameters (edema, cell migration, hypernociception, histopathological analyzes) were made from 0 to 24 hours, and until the 14th day, for others evaluations (hematological, plasma biochemical, histopathological and behavioral parameters). The results of the study showed that tea and polysaccharides from X. americana inhibited inflammatory parameters such as edema, cell migration and pain, both visceral and articular, induced by zimosan. In addition, the data also suggest that the use of tea by mouth is relatively safe, as it has not shown any lethality, or has induced significant physiological and/or behavioral changes in animals. This study is relevant because it scientifically validates the popular use of this plant in inflammatory and painful processes.